Measuring the Risk Dimension of Investment Performance - Robinson, Randall S. (Journal of Finance, 1970)
Randall S. Robinson, Measuring the Risk Dimension of Investment Performance, The Journal of Finance, Vol. 25, No. 2, Papers and Proceedings of the Twenty-Eighth Annual Meeting of the American Finance Association New York, N.Y. December, 28-30, 1969 (May, 1970), pp. 455-467